Challenges Affecting Implementation of Strategic Plan in Kenya Health Sector; A Case of Public Hospitals in Machakaos County - Nzuki, Hellen; Ombuki, Charles; Arasa, Robert (Noble Academic Publisher, 2017)
Strategic planning and its implementation in Kenya at the Ministry of Health is an element of the on-going public sector reforms designed to improve the delivery of health care services. However, this implementation has been facing different challenges. This study sought to investigate these challenges with specific reference to hospitals in Machakos County. The objectives of the include: To assess how strategic plan awareness affects strategic plan implementation at Machakos County Public Hospitals; to assess the effect of human resource staffing norms in strategic plan, implementation at Machakos County Public Hospitals and to determine the extent to which organization structure affect strategic plan implementation at Machakos County public hospitals. The study employed a correlation research design in assessing the effect of various challenges on implementation of health sector strategic plans in Kenya. The target population comprised of officers at different management levels in Machakos County public Hospitals. Stratified random sampling was adopted were all officers with personal identification number based on different strata had an equal opportunity of taking part in the study. Major strata which were considered included doctors, clinical officers, nurses and support staff. Data was collected using a semistructured, questionnaire that was included with open-ended questions as well as closed-ended questions. The collected data was analyzed using descriptive and inferential statistics. The study findings revealed that staff awareness, human resource staffing norms and organizational structure have a significant effect on the implementation of strategic plans of hospitals in Machakos County and it suggested a number of recommendations in relation to the findings of the study
Keywords: Strategic Planning; Strategic Implementation; Kenya Health Policy Framework (KHPF); Kenya Vision 2030.